2002
DOI: 10.1095/biolreprod66.5.1531
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Expression of Messenger RNAs for the Peroxisome Proliferator-Activated Receptors in Ovarian Tissue from Naturally Cycling and Pseudopregnant Rats1

Abstract: Structural and functional development of the corpus luteum (CL) involves tissue remodeling, angiogenesis, lipid metabolism, and steroid production. The peroxisome proliferator-activated receptors (PPARs) have been shown to play a role in these as well as in a multitude of other cellular processes. To examine the expression of mRNA corresponding to the PPAR family members (alpha, delta, and gamma) in luteal tissue, ovaries were collected from gonadotropin-treated, immature rats on Days 1, 4, 8, and 14 of pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 48 publications
(66 reference statements)
6
34
0
4
Order By: Relevance
“…PPARg was also identified in luteal tissue of the naturally cycling rat (Komar & Curry 2002). Interestingly, the expression of mRNA for PPARg was higher in luteal tissue from previous ovulations compared with luteal tissue forming from the most recent ovulation (Komar & Curry 2002).…”
Section: Introductionmentioning
confidence: 92%
“…PPARg was also identified in luteal tissue of the naturally cycling rat (Komar & Curry 2002). Interestingly, the expression of mRNA for PPARg was higher in luteal tissue from previous ovulations compared with luteal tissue forming from the most recent ovulation (Komar & Curry 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Many studies have shown that PPARs gene and/or protein expression varies depending on ovarian cell type, physiological status and the species [14,[22][23][24][25][26]. It has also been frequently reported that PPARs are engaged in the regulation of various ovarian functions.…”
Section: Ppars In the Ovarymentioning
confidence: 99%
“…PPARs have three subtypes, a, b/d, and g (Issemann & Green 1990, Komar 2005, which are detected in the ovary of several species, including the rat (Komar 2005). PPARg is expressed primarily in the granulosa cells of developing follicles (Komar & Curry 2002), where it regulates the synthesis of steroid hormones (Huang 2008). At the end of follicular development, the luteinizing hormone surge downregulates the expression of ovarian PPARg (Komar et al 2001, Froment et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of follicular development, the luteinizing hormone surge downregulates the expression of ovarian PPARg (Komar et al 2001, Froment et al 2003. In the rat, PPARg expression is low in newly forming luteal tissue and higher in luteal tissue present from previous ovulations (Komar & Curry 2002).…”
Section: Introductionmentioning
confidence: 99%